A lithium-rich porous graphite material and its preparation method and application
By introducing transition metal particles and lithium-containing alkaline substances into the negative electrode material of the lithium-ion battery for chemical etching, lithium-rich porous graphite materials were prepared, which solved the material stability problem of lithium-ion batteries during high-rate charging and discharging, and achieved the improvement of high-rate performance and high reversible capacity.
Patent Information
- Application Number
- CN202210932639.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-04
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2042-08-04
AI Technical Summary
The negative electrode materials of existing lithium-ion batteries are prone to graphite expansion and fall off and metal lithium precipitation during high-speed charging and discharge, resulting in deterioration of the negative electrode interface and safety hazards, limiting the high-speed performance of lithium-ion batteries.
By compounding the transition metal particles with graphite and calcining under an inert atmosphere, chemical etching is performed using lithium-containing alkaline substances as etching agents to produce lithium-rich porous graphite material. This material has a large pore structure and lithium element distribution, which significantly shortens the lithium ion diffusion path and improves the rate performance.
The high-rate performance and high reversible charge and discharge capacity of lithium-ion batteries are achieved, which reduces the loss of Coulomb efficiency, and is low in cost because it does not use precious metal catalysts, which is suitable for large-scale industrial production.
Smart Images

Figure CN115483371B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a lithium-rich porous graphite material produced by etching a lithium-containing alkaline substance assisted by a transition metal, a preparation method and an application thereof, and belongs to the technical field of lithium ion batteries. Background Art
[0002] At present, the rapid development of electric passenger cars and portable electronic devices is severely restricted by the charging speed, so there is an urgent need to improve the charge and discharge rate of lithium-ion batteries. However, there is a lack of negative electrode materials that can achieve both high energy density and rate performance, which restricts the development of fast-charging lithium-ion batteries. Graphite has a high specific energy (360W·h·Kg -1 ), with low operating voltage, low cost and good safety, is an ideal negative electrode for lithium-ion batteries. Modification of the graphite negative electrode to improve rate performance is expected to take into account both energy density and rate performance to meet the needs of fast-charging lithium-ion batteries.
[0003] However, due to the high migration energy of lithium ions in graphite, graphite will expand and fall off during high current charging, and even metal lithium will precipitate on the negative electrode surface. The precipitation of metal lithium causes serious deterioration of the negative electrode interface. In addition, dendrite growth will also cause safety hazards, seriously affecting the high-rate performance of lithium-ion batteries. Therefore, it is necessary to modify the graphite material and shorten the lithium ion diffusion path to improve its rate performance. Currently, there are two main methods: ultrafine grinding and etching.
[0004] Chen Chen et al. used petroleum coke, asphalt coke or needle coke as precursors in "A Method for Preparing High-Rate Fast-Charging Graphite Negative Electrode Materials" (Chinese Patent Publication No. CN112289986A), ball-milled, shaped, and then mixed with a carbon source for graphitization to obtain a spherical graphite powder with a higher rate. This method improves the rate performance by reducing the graphite particle size, but at the same time, the method shapes and coats the precursor to reduce the decrease in the first-cycle coulomb efficiency caused by excessive surface area, thereby sacrificing some of the rate performance. In addition, the graphitization process requires high-temperature treatment of the material, and the treatment temperature is often above 2000°C, which greatly increases energy consumption.
[0005] Song Huaihe et al. used laser to etch graphite in "A Method for Modifying Graphite Negative Electrode Sheets for Lithium-ion Batteries" (China Patent Publication No. CN114005963A). The channels produced by etching increased the lithium ion diffusion channels without significantly increasing the surface area and reducing the first coulomb efficiency, thereby achieving better rate performance. However, this technology uses laser etching, which is costly. Liu Mengyang et al. "A Method for Preparing Fast-charging Graphite Negative Electrode Materials" (China Patent Publication No. CN112713270A) mixed alkaline substances with graphite, and then activated the graphite by high-temperature treatment, achieving better rate performance. However, high-temperature alkaline activation treatment can only increase the surface lithium insertion sites, and cannot significantly shorten the lithium ion diffusion path, so the improvement of rate performance is limited. Zhang Tao et al. "A Method for Preparing Porous Carbon Materials by Non-precious Metal-assisted Chemical Etching" (China Patent Publication No. CN111732102A) introduced transition metals as catalysts, used potassium hydroxide as an etchant, and directionally etched the carbon material at high temperature to produce controllable large pores and deep holes. However, etching graphite with potassium hydroxide will leave potassium ions in the graphite sheets, hindering the transmission of lithium ions and adversely affecting the rate performance and charge and discharge capacity. Summary of the invention
[0006] In view of the defects of the above-mentioned current technologies, the purpose of the present invention is to provide a lithium-rich porous graphite and a preparation method and application thereof.
[0007] In a first aspect, the present invention provides a lithium-rich porous graphite material, which comprises: a porous graphite material and lithium elements distributed on the surface or between layers of the porous graphite material; the porous graphite material has a macroporous structure; wherein the lithium element exists in the form of lithiated graphite or lithium oxide, and the molar content of the lithium element is 2 to 10% of the total elements.
[0008] In the present invention, the lithium-rich porous graphite has abundant macropores and deep pores, which significantly increases the lithium ion mass transfer channel, shortens the lithium ion diffusion path, and can achieve a higher charge and discharge rate. Chemical etching of lithium-containing alkaline substances introduces defects in the porous graphite that can accommodate the reversible deintercalation of lithium ions, so that the porous graphite has a higher reversible charge and discharge capacity. At the same time, the porous graphite contains lithiated graphite or lithium oxide produced during the etching process as an additional lithium source, which supplements the coulomb efficiency loss during the first cycle.
[0009] Preferably, the pore size of the macropores is between 10 nm and 2 μm.
[0010] Preferably, the rate performance of the lithium-rich porous graphite material is a reversible capacity of 220 mA·h·g at 1C. -1 ; The Coulomb efficiency of the lithium-rich porous graphite material is 87% to 99.7%.
[0011] Preferably, the lithium element is generated in-situ on the surface or between layers of graphite after calcining a lithium-containing alkaline substance and graphite loaded with transition metal particles.
[0012] In a second aspect, the present invention provides a method for preparing a lithium-rich porous graphite material, comprising:
[0013] (1) mixing and stirring the graphite loaded with transition metal particles and the aqueous solution of the lithium-containing alkaline substance, drying the mixture, transferring the mixture to a crucible, calcining the mixture under an inert atmosphere, and cooling the mixture naturally to obtain a coarsely etched graphite;
[0014] (2) After the obtained coarsely etched graphite is cleaned, an oxidizing solution is used to dissolve the transition metal particles, and then the raw graphite is cleaned and dried for a second time to obtain the lithium-rich porous graphite material.
[0015] In the present invention, a transition metal salt is compounded with graphite, and the transition metal salt is pyrolyzed under an inert atmosphere to produce transition metal particles on the graphite surface. Subsequently, the composite is mixed with a lithium-containing alkaline substance, and then subjected to high temperature treatment. Since the transition metal particles can catalyze the activation of carbon materials, at a relatively low temperature, at the position where the transition metal particles are loaded, the lithium-containing alkaline substance will continue to react with the carbon atoms in the graphite, generating lithiated graphite and lithium oxides, while etching the graphite surface to produce macropores. After the reaction is completed, the transition metal particles are dissolved by washing and oxidant treatment to obtain the lithium-containing porous graphite.
[0016] Preferably, the composition of the transition metal particles in the graphite loaded with transition metal particles is selected from at least one of the transition metals Ni, Cu, Fe, Co, Mn, Mo, Ru, Au, and Pt; the particle size of the transition metal particles is 5 nm to 2 μm; and the loading amount of the transition metal particles is 5 to 25 wt%.
[0017] Preferably, the preparation method of the graphite loaded with transition metal particles comprises: mixing graphite powder and metal salt solution, stirring and drying at 60-90°C for 1-20 hours, transferring to a crucible, placing in an inert atmosphere, high temperature treatment at 400-800°C, and naturally cooling to obtain graphite loaded with transition metal particles.
[0018] Preferably, the graphite powder is artificial graphite or natural graphite, and its particle size is 3 to 50 μm; preferably, artificial spherical graphite with a particle size of 5 to 10 μm;
[0019] The metal salt in the metal salt solution is an organic salt or / inorganic salt of a metal element, preferably at least one of a formate of a metal element, an acetate of a metal element, an ethanolate of a metal element, a citrate of a metal element, an acetylacetonate of a metal element, a hydrochloride of a metal element, a sulfate of a metal element, a nitrate of a metal element, a phosphate of a metal element, a hypophosphite of a metal element, a chlorate of a metal element, a perchlorate of a metal element and an aminosulfonate of a metal element; the metal element is selected from at least one of Ni, Cu, Fe, Co, Mn, Mo, Ru, Au and Pt;
[0020] The solvent of the metal salt solution is at least one of water, ethanol and acetone;
[0021] The molar ratio of the metal salt to the graphite powder is 1:10 to 1:100;
[0022] The inert atmosphere is at least one of argon, nitrogen, helium, and carbon monoxide (CO);
[0023] The temperature of the high temperature treatment is 400°C to 1000°C / min, the holding time is 1 to 10 hours, and the preferred heating rate is 1°C / min to 20°C / min;
[0024] Preferably, the temperature of the high temperature treatment is 500-700° C., the holding time is 1-4 hours, and the heating rate is 5-10° C. / min.
[0025] Preferably, the lithium-containing alkaline substance comprises at least one of lithium hydroxide or a lithium compound; the molar ratio of the lithium-containing alkaline substance to the graphite in the graphite loaded with transition metal particles is 1:10 to 10:1;
[0026] Preferably, the lithium-containing alkaline substance is lithium hydroxide or a mixture of lithium hydroxide and sodium hydroxide;
[0027] Preferably, the molar ratio of the lithium-containing alkaline substance to the graphite in the graphite loaded with transition metal particles is 2:1 to 1:2;
[0028] The concentration of the aqueous solution containing lithium alkaline substance is 1 to 6 mol / L;
[0029] The linear speed of the stirring and drying is 0.5-3 m / s, the drying temperature is 80-120°C, and the drying time is 1-4 hours. Under the action of the lithium-containing alkaline substance as an etchant, the porous graphite has more defects of reversible lithium ion insertion and extraction, and therefore has a higher reversible charge and discharge specific capacity; the macropores produced by etching are conducive to the diffusion of lithium ions, which significantly improves the rate performance of lithium-rich porous graphite. The lithium-containing alkaline substance as an etchant can supplement lithium for graphite during the etching process, further suppressing the reduction of the coulombic efficiency of the porous graphite.
[0030] Preferably, the calcination temperature is 600-1000°C / min, the holding time is 2-16h, and the heating rate is preferably 1-20°C / min;
[0031] Preferably, the calcination treatment temperature is 700-900° C., the holding time is 6-10 hours, and more preferably the heating rate is 5-10° C. / min.
[0032] Preferably, the oxidant in the oxidizing solution is at least one of ferric chloride, potassium dichromate, hydrogen peroxide, sulfuric acid, and nitric acid;
[0033] The solvent in the oxidizing solution is selected from ethanol or water;
[0034] The concentration of the oxidizing solution is 0.1 to 5 mol / L;
[0035] The dissolving temperature is 40 to 80° C. and the dissolving time is 4 to 20 hours.
[0036] In a third aspect, the present invention provides a negative electrode sheet for a lithium battery, comprising the above-mentioned lithium-rich porous graphite material.
[0037] In a fourth aspect, the present invention provides a lithium battery comprising the above-mentioned negative electrode sheet for lithium battery.
[0038] Beneficial effects of the present invention:
[0039] (1) The etchant used in the present invention contains lithium. Under the catalytic action of transition metal particles, the lithium-containing alkaline substance has a strong reactivity with graphite, and can produce defects in the graphite that can accommodate the reversible deintercalation of lithium ions. At the same time, lithium ions can be replenished into the graphite negative electrode to replenish the irreversible lithium loss caused by the formation of the interface layer in the first cycle, thereby improving the first coulombic efficiency. It is worth noting that compared with the etching of graphite by transition metal-catalyzed potassium hydroxide, the etching of lithium-containing alkaline substances will not leave chemically inert potassium ions between the graphite layers, thereby more effectively achieving the improvement of reversible charge and discharge capacity and rate performance;
[0040] (2) Under the catalysis of transition metal particles, the reaction temperature of lithium-containing alkaline substances and graphite is reduced. Compared with other methods of activating graphite using lithium-containing alkaline substances, the present invention reduces the activation temperature or activation time while achieving the same or similar effects, thereby reducing production energy consumption;
[0041] (3) The etching method shortens the lithium ion diffusion path while increasing the specific surface area to a small extent, which is an ideal way to improve the rate performance of graphite negative electrodes. Compared with other etching methods such as laser etching, the preparation method of porous graphite provided by the present invention belongs to the chemical etching method. The raw materials and equipment used are simple and easy to obtain. The preparation method is simple and easy to operate, and the product consistency is good, which is suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 This is a scanning electron microscope image of the lithium-rich porous graphite in the preferred embodiment 1 of the present invention;
[0043] Figure 2 This is a scanning electron microscope image of graphite obtained by potassium hydroxide etching in Comparative Example 1;
[0044] Figure 3 is a scanning electron microscope image of the original graphite in Comparative Example 2;
[0045] Figure 4 This is a scanning electron microscope image of graphite treated with lithium hydroxide in Comparative Example 3;
[0046] Figure 5 This is a graph showing the content of each element in the lithium-rich porous graphite in the preferred embodiment 1 of the present invention;
[0047] Figure 6 The half-cell rate performance curves of the lithium-rich porous graphite in the preferred embodiment 1 of the present invention and the comparative examples 1 and 2 are shown;
[0048] Figure 7 The half-cell charge and discharge curve diagram of lithium-rich porous graphite in the preferred embodiment 1 of the present invention;
[0049] Figure 8 This is a half-cell charge and discharge curve diagram of graphite obtained by potassium hydroxide etching in Comparative Example 1 of the present invention;
[0050] Fig. 9 This is a half-cell charge and discharge curve diagram of the original graphite in Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0051] The present invention is further described below by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention.
[0052] In the present disclosure, the lithium-rich porous graphite material contains macropores produced by etching of lithium-containing alkaline substances catalyzed by transition metal particles, and the pore diameter is between 10nm and 2μm. Among them, lithium-rich refers to the lithium element that remains on the surface or between the layers of graphite after the reaction of lithium-containing alkaline substances with graphite in the graphite, and its molar proportion is 2 to 10at% of the total mass of the elements. The total elements of the lithium-rich porous graphite material include C element, O element, Li element and transition metal elements (including at least one of Ni, Cu, Fe, Co, Mn, Mo, Ru, Au, and Pt). Due to the lack of cleaning, a very small amount of transition metal elements will remain, and its content is 0 to 1at% of the total element content.").
[0053] In the present invention, the lithium-rich porous graphite material contains abundant macropores, abundant lithium ion transmission channels, and a short lithium ion diffusion path, so it has good rate performance; a large number of defects are formed during the etching process to accommodate the reversible insertion and extraction of lithium ions, and has a higher discharge specific capacity; at the same time, the porous graphite has additional lithium source supplementation and has a higher first coulomb efficiency (87% to 99.7%).
[0054] The present invention provides a method for obtaining a lithium-rich porous graphite negative electrode material with high rate and high capacity by using a lithium-containing alkaline substance as an etchant and metal particles on the surface of graphite to provide catalysis, and realizing directional etching to produce abundant macropores during calcination treatment. The present invention proposes for the first time an etchant for lithium hydroxide in non-precious metal catalytic etching, and the elemental composition of LiOH determines that it will form lithiated graphite or lithium compounds during the etching process, thereby leaving lithium elements in the graphite material.
[0055] The graphite powder is mixed with a metal salt solution, and stirred and dried at 60 to 90°C for 1 to 20 hours, the purpose of which is to achieve uniform coating of the graphite powder with metal salts by a liquid phase method, thereby achieving uniform distribution of metal particles during pyrolysis. Among them, the graphite powder is artificial graphite or natural graphite, and its particle size is 3 to 50 μm. More preferably, the graphite powder used is artificial spherical graphite with a particle size of 5 to 10 μm. The metal salt in the metal salt solution is an organic salt of transition metals Ni, Cu, Fe, Co, Mn, Mo, Ru, Au, Pt (such as formate, acetate, ethanolate, citrate and acetylacetonate, or inorganic salts such as hydrochloride, sulfate, nitrate, phosphate, hypophosphite, chlorate, perchlorate and aminosulfonate, etc.). The molar ratio of metal salt to graphite can be 1:10 to 1:100. More preferably, the selected metal salt is nickel acetate. The molar ratio of the metal salt to the graphite is 1:40. The solvent in the metal salt solution is one or more of water, ethanol and acetone. More preferably, the selected solvent is a mixture of water and alcohol in a volume ratio of 9:1. The metal particles loaded by the impregnation method are not as uniform as those by the stirring and drying method, and the metal loading amount and the size of the metal particles are difficult to control; secondly, compared with self-supporting carbon materials, it is difficult to apply the impregnation method to graphite powder.
[0056] The mixture obtained by stirring and drying is transferred to a crucible, and then placed in a heating furnace for high-temperature treatment at 400-800°C under an inert atmosphere, and a graphite precursor loaded with transition metal particles is obtained after natural cooling. The heating furnace used is a tubular furnace, a roller kiln, a tunnel kiln, a push plate kiln, a shuttle furnace or a rotary kiln, and the inert atmosphere used is one or more of argon, nitrogen, helium, and carbon monoxide. The parameters of the high-temperature treatment include: a heating rate of 1°C / min to 20°C / min, a target temperature of 400°C to 1000°C / min, and a holding time of 1 to 10h. More preferably, the heating rate is 5 to 10°C / min, the target temperature is 500 to 700°C, and the holding time is 1 to 4h.
[0057] The graphite precursor loaded with transition metal particles is mixed with a lithium-containing alkaline solution, stirred and dried, and then transferred to a crucible, then placed in a heating furnace for calcination under an inert atmosphere, and naturally cooled to obtain rough etched graphite. The alkaline substance includes one or more of lithium hydroxide or lithium compounds, and the molar ratio of the lithium-containing alkaline substance to graphite is 1:10-10:1; more preferably, the alkaline substance is lithium hydroxide or a mixture of lithium hydroxide and sodium hydroxide, and the molar ratio of the lithium-containing alkaline substance to graphite is 2:1-1:2. Among them, the mixing is to put the graphite precursor into a lithium-containing alkaline aqueous solution (with a concentration of 1 to 6 mol / L) and stir and dry, the stirring line speed is 0.5 to 3 m / s, the drying temperature is 80 to 120°C, and the drying time is 1 to 4h. The crucible used is a corundum crucible, a magnesium oxide crucible, a nickel crucible or a platinum crucible. More preferably, the crucible used is a nickel crucible. The parameters of the calcination treatment include: a heating rate of 1 to 20°C / min, a target temperature of 600 to 1000°C / min, and a holding time of 2 to 16 hours. More preferably, the heating rate is 5 to 10°C / min, the target temperature is 700 to 900°C, and the holding time is 6 to 10 hours. Lithium hydroxide can construct channels in graphite under transition metal catalysis, while no channels are formed without transition metals. At the same time, transition metal catalysis reduces the temperature of the reaction between lithium hydroxide and carbon, and increases the residual amount of lithium ions, which plays a significant role.
[0058] After the coarse etched graphite is washed with deionized water, an oxidizing solution is used to dissolve the transition metal particles. The material is then washed twice with deionized water and dried to obtain a lithium-rich porous graphite material. The washing is performed using industrial water or deionized water, and the washing is performed by filtering or centrifugation. The oxidizing solution can be an ethanol or aqueous solution of ferric chloride, potassium dichromate, hydrogen peroxide, sulfuric acid, or nitric acid, and the solution concentration is 0.1 to 5 mol / L. The dissolution temperature can be 40 to 80°C, and the time can be 4 to 20 hours.
[0059] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0060] The lithium-rich porous graphite material in the present invention does not contain impurities, and the final product is lithium-rich porous graphite containing porous graphite particles with abundant macropores and deep pores. The porous graphite has good rate performance and improved reversible charge and discharge capacity; at the same time, it has additional lithium source supplementation, low first irreversible capacity, and high first coulomb efficiency.
[0061] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values exemplified below.
[0062] Example 1
[0063] (1) 0.622 g of nickel acetate tetrahydrate (0.0025 mol) was dissolved in a mixture of 9 mL of water and 1 mL of alcohol to obtain solution A, and then 1.2 g (0.1 mol) of graphite powder was dispersed in solution A and stirred and dried at 80° C. for 2 h to obtain precursor A after drying;
[0064] (2) The obtained precursor A was placed in a corundum crucible with a cover, placed in a vacuum tube heating furnace, and introduced with inert atmosphere argon gas at a flow rate of 60 mL / min. The heating program was set to a heating rate of 5°C / min, and the temperature was raised to 600°C in 2 h. After keeping the temperature for 2 h, the precursor was naturally cooled to obtain the precursor B;
[0065] (3) Mix the obtained precursor B with 33mL, 3mol / L lithium hydroxide aqueous solution (0.01mol), add 2mL of anhydrous ethanol, and stir to dry. The stirring line speed is 0.5m / s, the heating temperature is 100°C, and the heating time is 2h. After drying, the obtained material is transferred to a nickel crucible, placed in a vacuum tube heating furnace, and an inert atmosphere of argon is introduced at a flow rate of 60mL / min. Set the heating program to a heating rate of 5°C / min, heat to 800°C in 2.7h, keep warm for 6h, and then cool naturally to obtain precursor C;
[0066] (4) Precursor C was taken out, and the residual alkaline substances were washed away with water. The washed material was then placed in 20 mL, 0.1 mol / L ferric chloride ethanol solution, heated to 60° C., and continued for 4 hours. After the dissolution was completed, the mixture was filtered to separate the acid solution, and then the graphite was washed 3 times with deionized water. After drying, a lithium-rich porous graphite material was obtained. The molar content of lithium in the final lithium-rich porous graphite was 3.67%.
[0067] Comparative Example 1
[0068] (1) 0.622 g of nickel acetate tetrahydrate was dissolved in a mixture of 9 mL of water and 1 mL of alcohol to obtain solution A, and then 1.2 g of graphite powder was dispersed in solution A and stirred and dried at 80° C. for 2 h to obtain precursor A after drying;
[0069] (2) Precursor A was placed in a corundum crucible with a lid, placed in a vacuum tube heating furnace, and introduced with inert argon gas at a flow rate of 60 mL / min. The heating program was set to a heating rate of 5°C / min, and the temperature was raised to 600°C in 2 h. After keeping the temperature for 2 h, the precursor was naturally cooled to obtain precursor B;
[0070] (3) Mix the precursor B with 17 mL of 6 mol / L potassium hydroxide aqueous solution, add 2 mL of anhydrous ethanol, and stir to dry. The stirring line speed is 0.5 m / s, the heating temperature is 100 ° C, and the heating time is 2 h. After drying, the obtained material is transferred to a nickel crucible, placed in a vacuum tube heating furnace, and an inert atmosphere of argon is introduced at a flow rate of 60 mL / min. The heating program is set to a heating rate of 5 ° C / min, and the temperature is raised to 800 ° C in 2.7 h. After keeping the temperature for 6 h, it is naturally cooled to obtain the precursor C;
[0071] (4) Precursor C was taken out, and the residual alkaline substances were washed away with water. The washed material was then placed in 20 mL, 0.5 mol / L ferric chloride ethanol solution, heated to 60 ° C, and continued for 4 hours. After the dissolution was completed, the mixture was filtered to separate the acid solution, and then the graphite was washed 3 times with deionized water, and a porous non-lithium-rich graphite material was obtained after drying.
[0072] Comparative Example 2
[0073] The raw graphite was washed three times with deionized water and dried to obtain untreated graphite as Comparative Example 2.
[0074] Comparative Example 3
[0075] Mix the raw graphite with 33mL, 3mol / L lithium hydroxide aqueous solution, add 2mL anhydrous ethanol, and stir to dry. The stirring line speed is 0.5m / s, the heating temperature is 100℃, and the heating time is 2h. After drying, the obtained material is transferred to a nickel crucible, placed in a vacuum tube heating furnace, and an inert atmosphere of argon is introduced at a flow rate of 60mL / min. Set the heating program to a heating rate of 5℃ / min, heat to 800℃ in 2.7h, keep warm for 6h, and then cool naturally. Wash away the residual alkaline substances with water to obtain a graphite material treated with lithium hydroxide.
[0076] Preparation of the negative electrode sheet of the battery: 0.96 g of the porous graphite material obtained in Example 1 or Comparative Examples 1-3, 0.015 g of carboxymethyl cellulose, and 0.025 g of styrene-butadiene rubber were dissolved in 3 mL of deionized water and stirred for 48 h. The resulting mixture was then coated on a copper foil using a 100 μm scraper and dried at 60° C. to obtain the desired negative electrode sheet.
[0077] The performance test was conducted in a button lithium-ion battery. The battery was assembled as follows: lithium sheet was used as the counter electrode, Celgard2300 was used as the separator, and the electrolyte was an EC-DEC (volume ratio 1:1) solution containing 1M LiPF6, where LiPF6 is lithium hexafluorophosphate, EC is ethylene carbonate, and DEC is diethyl carbonate. During the test, the temperature was room temperature, constant current charging and discharging was used, and the charging and discharging rates were 0.1C, 0.5C, 1.0C, 2.0C, 5.0C, and 8.0C, and the voltage control range was 0.005-2V.
[0078] Figure 1 This is a scanning electron microscope image of lithium-rich porous graphite in the preferred embodiment 1 of the present invention. As shown in the figure, the surface of lithium-rich porous graphite is rich in macropores, which is conducive to lithium ion transmission.
[0079] Figure 2 This is a scanning electron microscope image of graphite obtained by potassium hydroxide etching in Comparative Example 1. It can be seen from the image that potassium hydroxide etches abundant pores on the graphite surface.
[0080] Figure 3 This is a scanning electron microscope image of the original graphite in Comparative Example 2. It can be seen from the image that the original morphology of the graphite is complete and has no holes.
[0081] Figure 4 This is a scanning electron microscope image of the graphite obtained by lithium hydroxide treatment in Comparative Example 3. It can be seen from the image that when there is no transition metal catalyst, lithium hydroxide treatment cannot etch and form holes on the graphite surface.
[0082] Figure 5 This is a diagram of the content of each element in the lithium-rich porous graphite in the preferred embodiment 1 of the present invention. The X-ray photoelectron spectrum of the obtained lithium-rich porous graphite has lithium element signals detected, with a molar ratio of about 3.67%. At the same time, oxygen elements are also detected, corresponding to the lithium oxide contained.
[0083] Figure 6 This is a half-cell rate performance curve diagram of the lithium-rich porous graphite in the preferred embodiment 1 of the present invention and the comparative examples 1 and 2. It can be seen from the figure that the obtained porous graphite has a significant improvement in rate performance, with a capacity increase of 53% at 0.5C and a capacity increase of 72% at 1C.
[0084] Figure 7The half-cell charge and discharge curve of the lithium-rich porous graphite in the preferred embodiment 1 of the present invention shows that the obtained lithium-rich porous graphite has a significant improvement in reversible charge and discharge capacity and first coulomb efficiency compared with comparative example 2, and has a significant improvement in reversible charge and discharge capacity compared with comparative example 1. The lithium-rich porous graphite can achieve 395mA·h·g -1 The reversible charge and discharge capacity of the battery is 410 mA·h·g. The first coulomb efficiency is 87%. As the number of cycles increases, the reversible capacity increases gradually. The reversible charge and discharge capacity of the third cycle increases to 410 mA·h·g -1 , the Coulomb efficiency reaches 99.7%.
[0085] Figure 8 This is a half-cell charge and discharge curve diagram of comparative example 1 of the present invention. It can be seen from the diagram that the first coulombic efficiency and reversible charge and discharge capacity of the graphite obtained by potassium hydroxide etching are significantly reduced compared with the original graphite in comparative example 2.
[0086] Fig. 9 This is the half-cell charge and discharge curve of comparative example 2 of the present invention. It can be seen from the figure that the initial coulombic efficiency of the original graphite is relatively high (up to 94%), but the reversible capacity is only 274 mA·h·g -1 .
[0087] Example 2
[0088] (1) 1.40 g of ferric sulfate nonahydrate was dissolved in 10 mL of water to obtain solution A, and then 1.2 g of graphite powder was dispersed in solution A and stirred and dried at 80° C. for 4 h to obtain precursor A after drying;
[0089] (2) Precursor A was placed in a corundum crucible with a lid, placed in a vacuum tube heating furnace, and introduced with inert atmosphere argon at a flow rate of 60 mL / min. The heating program was set to a heating rate of 5°C / min, and the temperature was raised to 900°C in 3 h. After keeping the temperature for 2 h, the precursor was naturally cooled to obtain precursor B;
[0090] (3) Precursor B was mixed with 17 mL of 3 mol / L LiOH aqueous solution and 5.5 mL of 9 mol / L NaOH aqueous solution, and stirred to dry. The stirring line speed was 1 m / s, the heating temperature was 100 °C, and the heating time was 4 h. After drying, the obtained material was transferred to a nickel crucible, placed in a vacuum tube heating furnace, and an inert atmosphere of argon was introduced at a flow rate of 60 mL / min. The heating program was set to a heating rate of 5 °C / min, and the temperature was raised to 800 °C in 2.7 h. After keeping the temperature for 12 h, the mixture was naturally cooled to obtain precursor C.
[0091] (4) Precursor C was taken out, and the residual alkaline substances were washed with water, and then the washed material was placed in a 0.1 mol / L ferric chloride ethanol solution, heated to 60°C, and kept warm for 4 hours. After the dissolution was completed, the mixture was filtered and separated, and then the graphite was washed with deionized water for 3 times, and the lithium-rich porous graphite was obtained after drying. The molar content of lithium in the finally obtained lithium-rich porous graphite was 3.8%.
[0092] Example 3
[0093] (1) 38.5 g of nickel sulfate was dissolved in 500 mL of water and 50 mL of anhydrous ethanol to obtain solution A, and then 120 g of graphite powder was dispersed in solution A and stirred and dried at 100° C. for 8 h to obtain precursor A after drying;
[0094] (2) Precursor A was placed in a corundum crucible with a lid, placed in a vacuum tube heating furnace, and introduced with inert nitrogen gas at a flow rate of 60 mL / min. The heating program was set to a heating rate of 5°C / min, and the temperature was raised to 600°C in 2 h. After keeping the temperature for 5 h, the precursor was naturally cooled to obtain precursor B;
[0095] (3) Mix the precursor B with 1100mL of 3mol / L lithium hydroxide aqueous solution, add 50mL of anhydrous ethanol, and stir to dry. The stirring line speed is 3m / s, the heating temperature is 100°C, and the heating time is 10h. After drying, the obtained material is transferred to a nickel crucible, placed in a vacuum tube heating furnace, and an inert atmosphere of argon is introduced at a flow rate of 60mL / min. Set the heating program to a heating rate of 5°C / min, heat to 900°C in 3h, keep warm for 10h, and then cool naturally to obtain the precursor C;
[0096] (4) Precursor C is taken out, and the residual alkaline substances are washed away with water, and then the washed material is placed in a 0.5 mol / L potassium dichromate solution, heated to 80°C, and kept warm for 4 hours. After the dissolution is completed, the mixture is filtered and separated, and then the graphite is washed with deionized water for 3 times, and the lithium-rich porous graphite is obtained after drying. The molar content of lithium in the finally obtained lithium-rich porous graphite is 5.5%.
[0097] Example 4
[0098] The preparation process of lithium-rich porous graphite in this embodiment 4 is different from that in Example 1 only in that: in step (3), a precursor B containing 1.2g of raw graphite is mixed with 66mL, 3mol / L lithium hydroxide aqueous solution, 6mL of anhydrous ethanol is added, and the mixture is stirred and dried. The stirring linear velocity is 3m / s, the heating temperature is 100°C, the heating time is 2h, and the resulting material is transferred to a nickel crucible after drying, placed in a vacuum tube heating furnace, and an inert atmosphere of argon is introduced at a flow rate of 60mL / min. The heating program is set to a heating rate of 5°C / min, and the temperature is raised to 900°C in 3h. After being kept warm for 10h, it is naturally cooled to obtain a precursor C. The molar content of lithium in the finally obtained lithium-rich porous graphite is 8.7%.
[0099] The preferred specific embodiments of the present invention are described in detail above. It should be understood that ordinary technicians in the field can make many modifications and changes based on the concept of the present invention without creative work. Therefore, all technical solutions that can be obtained by technicians in the technical field based on the concept of the present invention through logical analysis, reasoning or limited experiments on the basis of the prior art should be within the scope of protection determined by the claims.
Claims
1. A method for preparing a lithium-rich porous graphite material, characterized in that: The lithium-rich porous graphite material comprises: a porous graphite material and lithium elements distributed on the surface or between layers of the porous graphite material; the porous graphite material has a macroporous structure; wherein the lithium element exists in the form of lithiated graphite or lithium oxide, and the molar content of the lithium element is 2-10% of the total elements; The preparation method comprises: (1) mixing graphite loaded with transition metal particles and an aqueous solution of a lithium-containing alkaline substance, stirring and drying, then transferring the mixture into a crucible, placing the mixture in an inert atmosphere for calcination, and cooling the mixture naturally to obtain a coarsely etched graphite; the lithium-containing alkaline substance is lithium hydroxide or a mixture of lithium hydroxide and sodium hydroxide; (2) After the obtained coarsely etched graphite is cleaned, an oxidizing solution is used to dissolve the transition metal particles, and then the raw graphite is cleaned and dried for a second time to obtain the lithium-rich porous graphite material.
2. The preparation method according to claim 1, characterized in that: The pore size of the macroporous structure is between 10 nm and 2 μm.
3. The preparation method according to claim 1, characterized in that The rate performance of the lithium-rich porous graphite material is a reversible capacity of 220 mA·h·g at 1C -1 ; The Coulomb efficiency of the lithium-rich porous graphite material is 87% to 99.7%.
4. The preparation method according to claim 1, characterized in that: The composition of the transition metal particles in the graphite loaded with transition metal particles is selected from at least one of transition metals Ni, Cu, Fe, Co, Mn, Mo, Ru, Au, and Pt; the particle size of the transition metal particles is 5 nm to 2 μm; and the loading amount of the transition metal particles is 5 to 25 wt%.
5. The preparation method according to claim 1, characterized in that: The preparation method of the graphite loaded with transition metal particles comprises: mixing graphite powder and metal salt solution, stirring and drying at 60-90° C. for 1-20 hours, transferring the mixture into a crucible, placing the mixture in an inert atmosphere, performing high temperature treatment at 400-800° C., and naturally cooling the mixture to obtain graphite loaded with transition metal particles.
6. The preparation method according to claim 5, characterized in that: The graphite powder is artificial graphite or natural graphite, and its particle size is 3 to 50 μm; The metal salt in the metal salt solution is an organic salt or / and an inorganic salt of a metal element; the metal element is selected from at least one of Ni, Cu, Fe, Co, Mn, Mo, Ru, Au, and Pt; The solvent of the metal salt solution is at least one of water, ethanol and acetone; The molar ratio of the metal salt to the graphite powder is 1:10 to 1:100; The inert atmosphere is at least one of argon, nitrogen, helium and carbon monoxide; The temperature of the high temperature treatment is 400° C. to 1000° C., the holding time is 1 to 10 hours, and the heating rate is 1° C. / min to 20° C. / min.
7. The preparation method according to claim 6, characterized in that The graphite powder is artificial spherical graphite with a particle size of 5 to 10 μm; the metal salt in the metal salt solution is at least one of metal formates, metal acetates, metal ethanolates, metal citrates, metal acetylacetonates, metal hydrochlorides, metal sulfates, metal nitrates, metal phosphates, metal hypophosphites, metal chlorates, metal perchlorates and metal sulfamate; the high temperature treatment temperature is 500 to 700° C., the insulation time is 1 to 4 hours, and the heating rate is 5 to 10° C. / min.
8. The preparation method according to claim 1, characterized in that: The molar ratio of the lithium-containing alkaline substance to the graphite in the graphite loaded with transition metal particles is 1:10 to 10:1; The concentration of the aqueous solution containing lithium alkaline substance is 1 to 6 mol / L; The linear speed of the stirring drying is 0.5-3 m / s, the drying temperature is 80-120° C., and the drying time is 1-4 hours.
9. The preparation method according to claim 8, characterized in that: The molar ratio of the lithium-containing alkaline substance to the graphite in the graphite loaded with transition metal particles is 2:1 to 1:
2.
10. The preparation method according to claim 1, characterized in that The calcination treatment temperature is 600-1000° C., the heat preservation time is 2-16 h, and the heating rate is 1-20° C. / min.
11. The preparation method according to claim 10, characterized in that The calcination treatment temperature is 700-900°C, the heat preservation time is 6-10 hours, and the heating rate is 5-10°C / min.
12. The preparation method according to claim 1, characterized in that: The oxidizing agent in the oxidizing solution is at least one of ferric chloride, potassium dichromate, hydrogen peroxide, sulfuric acid, and nitric acid; The solvent in the oxidizing solution is selected from ethanol or water; The concentration of the oxidizing solution is 0.1 to 5 mol / L; The dissolving temperature is 40 to 80° C. and the dissolving time is 4 to 20 hours.
13. A negative electrode sheet for a lithium battery, characterized in that: A lithium-rich porous graphite material obtained by the preparation method according to claim 1.
14. A lithium battery, characterized in that: A negative electrode sheet for a lithium battery comprising the negative electrode sheet according to claim 13.
Citation Information
Patent Citations
Method for preparing porous carbon material by ruthenium particle-assisted etching in strong alkali environment
CN111732102A
Preparation method of high-magnification quick-charging graphite negative electrode material
CN112289986A
Preparation method of quick-charging graphite negative electrode material
CN112713270A
Modification method of graphite negative plate of lithium ion battery
CN114005963A
Lithium-salt-modified lithium ion battery anode material and preparation method thereof
CN104393235A